2000
DOI: 10.3349/ymj.2000.41.1.34
|View full text |Cite
|
Sign up to set email alerts
|

The changing epidemiology of hepatitis A in children and the consideration of active immunization in Korea

Abstract: Currently, Korea is a low endemicity country for HAV, especially in children. However, recent reports of hepatitis A outbreaks show that there has been a shift of disease incidence to adolescents and young adults, with 2 cases of acute liver failure in one reported outbreak. We need to study the immune status for HAV in order to provide information for the establishment of preventive measures and possible consequences of HAV in Korea. A total of 334 infants, children and adolescents less than 20 years of age l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 1 publication
5
61
0
Order By: Relevance
“…Prevalence of HAV infection is not the same in different parts of the world (varies between 15% and 100%), and depends on geographic area, sanitary levels and socioeconomic conditions [4][5][6][7]. Meanwhile, a shifting epidemiological pattern from high to intermediate and low seropositivity has been shown in many countries, some of which are underdeveloped and developing countries [8,9]. Table 2 shows result by sex distribution of the study population.…”
Section: Methodsmentioning
confidence: 99%
“…Prevalence of HAV infection is not the same in different parts of the world (varies between 15% and 100%), and depends on geographic area, sanitary levels and socioeconomic conditions [4][5][6][7]. Meanwhile, a shifting epidemiological pattern from high to intermediate and low seropositivity has been shown in many countries, some of which are underdeveloped and developing countries [8,9]. Table 2 shows result by sex distribution of the study population.…”
Section: Methodsmentioning
confidence: 99%
“…However, neither socioeconomic status nor place of residence was associated with prevalence of HAV infection in our study. Most recent reports from Korea showed an extremely low rate of seroprevalence in young adults, 8,9,12,13 which suggests that these factors are no longer useful for predicting HAV infection in young adults.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] However, improvements in the socioeconomic status and general public health measures of Asian countries, including Korea, over the last 20 years has led to a shift in the seroprevalence of hepatitis A. [10][11][12][13] Recent reports from Korea suggest that Korea is in transition from a higher HAV endemic area to a lower one for HAV infection region, and that a growing number of young Korean adults are susceptible to HAV infection. 8 Currently in Korea, HAV vaccination is recommended for patients with chronic liver disease, and who are not immune to HAV.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis A is an acute, usually selflimiting disease of the liver caused by hepatitis A virus (HAV), a genus of picorna virus family. Improvements in hygienic conditions and effective health education results in increased number of susceptibles which may lead to an outbreak and become a problem in many developed countries especially in schools, day care centers and among high risk groups while a recent report from South Korea showed that outbreaks of Hepatitis A has shift from childhood to adolescents and young adults 1 Similarly reports from Shiraz city in south of Iran, indicated the rate of sero-prevalence was 68% among 15-year olds 2 . In another report from Tehran, the capital of Iran, the rate of exposure was 22.3% among school children 3 while a study from Delhi reported it 93.2% 4 .…”
mentioning
confidence: 99%